Menakar Nilai Kritis Fakruddin al-Razi dalam Tafsir Mafatih al-Ghayb - Nurman, Muhammad; Syafruddin, Syafruddin (Al - Tadabbur: Jurnal Ilmu Al-Qur'an dan Tafsir, 2021)
The Mafatih al-Ghayb Interpretation by Fakruddin al-Razi has been in spotlight among the Islamic scholars which raises pros and cons regarding its validity as an interpretation. This issue occured because Fakruddin al-Razi’s focus and way of presenting his interpretation is quite different compared to his predessesors. On the other hand, he seems to neglect his main focus in criticizing the thought of Muktazilah–one of famous sect in his period due to the broad exposure. Consequently, The Mafatih al-Ghayb Interpretation is known to be very trustworthy in quoting the opposing opinions, however it is blunt in its critical values.